Gastrointestinal parasites in backyard chickens of mid hill region of Meghalaya - M DAS; R LAHA; S DOLEY (Indian Journal of Animal Sciences, 2022)
The aim of the present study was to determine the prevalence of gastrointestinal (GI) parasites in the backyard chickens of mid hill region of Meghalaya. Fecal samples (2,290) were collected from different age groups, viz. < 8 weeks (694), 8–28 weeks (772) and > 28 weeks (824) and examined by flotation, sedimentation and modified McMaster techniques. Overall prevalence of GI parasitic infections was 37.20%. Eight species, viz. Eimeria sp. (30.16%), Heterakis gallinarum (14.08%), Ascaridia galli (21.36%), Strongyloides avium (12.44%), Capillaria sp. (7.51%), Raillietina sp. (8.56%), Syngamus trachea (3.52%) and Choanotaenia infundibulum (2.34%) were recorded. Age wise variations in infections were observed and trend was < 8 (25.64%), 8–28 (48.18%) and > 28 (38.71%) weeks old birds. Eimeria sp. was observed highest in both < 8 (67.97%) weeks and 8–28 (25.80%) weeks birds.A. galli (28.21%) was recorded highest in > 28 weeks old birds. The present study revealed that different species of GI parasites are prevalent throughout the year in the backyard chicken of mid hill region of Meghalaya, thus regular screening and deworming of bird is suggested for profitable backyard poultry farming.